Neuro-vascular coupling and heart rate variability in patients with type II diabetes at different stages of diabetic retinopathy - Hommer, Nikolaus; Kallab, Martin; Schlatter, Andreas; Janku, Patrick; Werkmeister, René M.; Howorka, Kinga; Schmidl, Doreen; Schmetterer, Leopold; Garhöfer, Gerhard (Frontiers in Medicine, 2022)
Aims/Hypothesis There is evidence that diabetes is accompanied by a break-down of functional hyperemia, an intrinsic mechanism of neural tissues to adapt blood flow to changing metabolic demands. However, to what extent functional hyperemia is altered in different stages of diabetic retinopathy (DR) in patients with type II diabetes is largely unknown. The current study set out to investigate flicker-induced retinal blood flow changes in patients with type II diabetes at different stages of DR. Materials and methods A total of 76 subjects were included in the present parallel-group study, of which 56 had diabetes with either no DR or different stages of non-proliferative DR (n = 29 no DR, 12 mild DR, 15 moderate to severe DR). In addition, 20 healthy subjects were included as controls. Retinal blood flow was assessed before and during visual stimulation using a combined measurement of retinal vessel calibers and blood velocity by the means of Doppler optical coherence tomography (OCT). To measure systemic autonomic nervous system function, heart rate variability (HRV) was assessed using a short-term orthostatic challenge test. Results In healthy controls, retinal blood flow increased by 40.4 ± 27.2% during flicker stimulation. Flicker responses in patients with DR were significantly decreased depending on the stage of the disease (no DR 37.7 ± 26.0%, mild DR 26.2 ± 28.2%, moderate to severe DR 22.3 ± 13.9%; p = 0.035, ANOVA). When assessing systemic autonomous neural function using HRV, normalized low frequency (LF) spectral power showed a significantly different response to the orthostatic maneuver in diabetic patients compared to healthy controls (p < 0.001). Conclusion/Interpretation Our study indicates that flicker induced hyperemia is reduced in patients with DR compared to healthy subjects. Further, this impairment is more pronounced with increasing severity of DR. Further studies are needed to elucidate mechanisms behind the reduced hyperemic response in patients with type II diabetes. Clinical trial registration [https://clinicaltrials.gov/], identifier [NCT03 552562].